2011
DOI: 10.1155/2011/283239
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Chronic Mucocutaneous Candidiasis Caused by Azole-ResistantCandida albicanswith Posaconazole

Abstract: Refractory or recurrent infections of skin, nails, and the mucous membranes are clinical signs of chronic mucocutaneous candidiasis, frequently associated with immunological defects. Here we describe a 39-years-old female patient, with familial CMC, that presented with an extensive infection caused by an azole-resistant Candida albicans isolate, successfully treated with posaconazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
0
6
0
3
Order By: Relevance
“…Previous studies had reported that patients with azole-resistant C . albicans infections can be cured with posaconazole [38], indicating a potential advantage of posaconazole against azole-resistant isolates. This feature was also supported by our finding that posaconazole treatment at a dose of 2 mg/kg (but not 0.5 mg/kg) exhibited therapeutic activity against the azole (especially fluconazole)-resistant isolate 12–99 (Figures 1B and 2B).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had reported that patients with azole-resistant C . albicans infections can be cured with posaconazole [38], indicating a potential advantage of posaconazole against azole-resistant isolates. This feature was also supported by our finding that posaconazole treatment at a dose of 2 mg/kg (but not 0.5 mg/kg) exhibited therapeutic activity against the azole (especially fluconazole)-resistant isolate 12–99 (Figures 1B and 2B).…”
Section: Discussionmentioning
confidence: 99%
“…However, this can lead to the development of drug‐resistant strains. Therefore, for this reason, other antifungals such as flucytosine, amphotericin, the new azoles such as voriconazole and posaconazole, and echinocandins have sometimes been used . Some patients with chronic mucocutaneous candidiasis also develop dermatophyte onychomycosis, which can also respond poorly to treatment.…”
Section: Treatmentsmentioning
confidence: 99%
“…Systemic agents (e.g. azole agents, echinocandins) are used for extensive or uncontrolled disease and for cases not responding to topical agents [153]. Invasive Candida infections must be treated intravenously (e.g.…”
Section: Treatment Of Fungal Diseases In Card9-deficient Patientsmentioning
confidence: 99%